2010
DOI: 10.1143/jjap.49.05fc03
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Study of Chemical–Mechanical Polishing Slurry of Cobalt Barrier Metal for the Next-Generation Interconnect Process

Abstract: This paper provides an overview of two topics. First, it presents a unified approach to various techniques addressing the non-uniqueness of the solution of the inverse gravimetric problem; alternative, simple proofs of some known results are also given. Second, it summarizes in a concise and self-contained way a particular multiscale regularization technique involving scaling functions and wavelets. 0266-5611/08/045019+25$30.00

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 2 publications
1
38
0
Order By: Relevance
“…At pH 4 and 7, the postpolish surface had much higher P/V and Sq values compare to that at pH 8. The higher roughness in the acidic region can be attributed to localized corrosion that was also reported by other authors 18,53,54 for PVD films. Indeed Co coupons (∼2 × 2 cm 2 ) simply dipped in 200 ml of 1 wt% H 2 O 2 + 1 wt% citric acid solution (stirred at 300 rpm) at pH 4, 7, or 8 for three minutes showed pits again at pH 4 and 7 but not at pH 8, as shown Figure 7 (panels d, e and f).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…At pH 4 and 7, the postpolish surface had much higher P/V and Sq values compare to that at pH 8. The higher roughness in the acidic region can be attributed to localized corrosion that was also reported by other authors 18,53,54 for PVD films. Indeed Co coupons (∼2 × 2 cm 2 ) simply dipped in 200 ml of 1 wt% H 2 O 2 + 1 wt% citric acid solution (stirred at 300 rpm) at pH 4, 7, or 8 for three minutes showed pits again at pH 4 and 7 but not at pH 8, as shown Figure 7 (panels d, e and f).…”
Section: Resultssupporting
confidence: 81%
“…Several authors [18][19][20][21][22][23][24][25][26] have investigated cobalt polishing for such applications where RR requirements are typically <20 nm/min and Co loss due to corrosion has to be as close to zero as possible, since even a minute loss of Co material can degrade the device reliability significantly. Hence, since the potential gap between Co and Cu is a large ∼0.61 V, it is very important to lower this to ∼10-20 mV.…”
mentioning
confidence: 99%
“…It was suggested to use alkaline slurry with low peroxide concentration. Nishizawa et al 13 reported the effects of H 2 O 2 and pH value on chemical mechanical polishing of cobalt. The results are similar as those of Ref.…”
mentioning
confidence: 99%
“…Only in this way can the dishing defects caused by the copper overburden CMP step be corrected, the residual copper be removed, and the surface non-uniformity of the patterned wafer be controlled. 49 Fig. 15 presents the removal rate for ruthenium and copper obtained using the slurries with various components (the specific information of slurries is embodied in the title of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to achieve planarization during barrier CMP, copper dishing, which is the height difference of a copper with respect to the adjacent oxides, must be controlled. [45][46][47][48][49] This would require that the removal rate of barrier material is greater than that of copper. Only in this way can the dishing defects caused by the copper overburden CMP step be corrected, the residual copper be removed, and the surface non-uniformity of the patterned wafer be controlled.…”
Section: Removal Rate Selectivitymentioning
confidence: 99%